The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/jfmk8030110
|View full text |Cite
|
Sign up to set email alerts
|

Transversus Abdominis Ultrasound Thickness during Popular Trunk–Pilates Exercises in Young and Middle-Aged Women

Abstract: The transversus abdominis (TrA) is a core muscle that contributes to functional mobility and lumbar stability. This study aimed to compare the changes in TrA thickness during different Pilates exercises, and to identify the exercise that elicited the greatest TrA activation. Forty-four healthy women were divided into two groups: young (25–35 years old) and middle-aged (36–55 years old). TrA thickness was assessed by ultrasound while the participants performed five Pilates exercises: basic position, hundred, hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Over the past few years, there has been a debate about the most effective motor control strategy to achieve the dynamic stabilization of the core [ 40 , 53 , 54 , 55 , 56 ]. This study’s findings confirm the third hypothesis as the average relative thickness of all three core muscles (TrA, IO, LM) was greater when using the hollowing compared to the bracing maneuver ( Figure 5 ), which is consistent with previous studies [ 15 , 32 ]. Some studies have suggested that deep abdominal muscles are activated to a greater extent by abdominal hollowing, while superficial muscles are activated to a greater extent by abdominal bracing [ 26 , 32 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Over the past few years, there has been a debate about the most effective motor control strategy to achieve the dynamic stabilization of the core [ 40 , 53 , 54 , 55 , 56 ]. This study’s findings confirm the third hypothesis as the average relative thickness of all three core muscles (TrA, IO, LM) was greater when using the hollowing compared to the bracing maneuver ( Figure 5 ), which is consistent with previous studies [ 15 , 32 ]. Some studies have suggested that deep abdominal muscles are activated to a greater extent by abdominal hollowing, while superficial muscles are activated to a greater extent by abdominal bracing [ 26 , 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…This study’s results have implications for individuals engaging in recreational exercise. These results contribute to the ongoing debate regarding the most effective motor control strategy for the dynamic stabilization of the core [ 14 , 15 , 28 , 29 ]. Specifically, for those looking to enhance core stability, the bird dog and side plank exercises, when combined with the hollowing maneuver, may be particularly advantageous.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations